Effect of Food Matrix on Regulation of Intestinal Barrier and Microbiota Homeostasis by Polysaccharides Sulfated Carrageenan - Xuke Shang; Juanjuan Guo; Peilin Chen (Foods)
Carrageenan (CGN) has side effects on the intestinal barrier. Damage to the intestinal barrier is associated with exposure to sulfate groups. Food matrix has significant influence on the exposure quantity of sulfate groups and conformation in κ-CGN, but the corresponding side effects are not reported specifically. This study aimed to explore the regulatory effect of κ-CGN dissolved in aqueous (κ-CGN) and in 3% casein (κ-carrageenan-casein, κ-CC) on the intestinal barrier and microbiota homeostasis. Research has shown that both κ-CGN and κ-CC can induce different extents of intestinal barrier damage through disrupting microbiota homeostasis. Importantly, κ-CGN in casein with lower sulfate groups content was found to repair the intestinal barrier injury induced by an equivalent dose of κ-CGN aqueous through increasing the abundance of Oscillibacter and decreasing Weissella. These alleviating effects were reflected in lower levels of tumor necrosis factor (TNF)-α and C-reaction protein (CRP), higher levels of interleukin (IL)-10, raised secretion of mucus and goblet cells, and improved expression of epithelial cell compact proteins zonula occluden (ZO)-1 and mucin protein 2 (MUC2). This study states that κ-CGN in casein has a positive regulatory effect on the intestinal barrier damage compared to in aqueous solution, which can provide guidance for processing and utilization of CGN.